Kebijakan Fiskal dan Moneter Indonesia serta Pengaruhnya terhadap Pasar Domestik di masa Pandemi COVID-19 - E. Mulya Samsul; Nur’aeni Nur’aeni; Ayu Indriani; Necayanti Necayanti (Jurnal Accounting Information System (AIMS), 2021)
This research aims to analyze Indonesia's fiscal policy as an important and alternative instrument carried out by the government and its influence on the domestic market in line with the monetary policy by the monetary authority of Bank Indonesia in the era of the COVID-19 pandemic, the combination of these policies must be strengthened in order to meet the country's stable economy. This study uses descriptive qualitative methods, namely methods to understand the various concepts found in the research process by using literature analysis and social phenomena research. The results showed that the efforts of the Government and monetary authorities in suppressing the impact of COVID-19 on the country's economy were pursued by strengthening the synergy between BI and the Ministry of Trade through strengthening the domestic market and export competitiveness. Followed by BI decided to maintain the BI 7- Day Reverse Rate (BI7DRR) as a new policy because it could quickly affect the money market and banking to the real sector.